A Currency Forward Contract. - Kamil, Anton Abdulbasah; Khor, Lian Peng (2003)
The aim of the paper is to present one out of conceivable approaches to problems of foreign exchange rates and subsequently forward contracts on them Our approach based on stochastic analysis, provides an untraditional view of the issues. Within the framework of this paper we model the exchange rate on the basis of the geometric Brownian motion. Obtained results entitle the use as a complementary tool when managing the exchange risk.